A Study of Cyclists, Participation Motivation, Serious Leisure and Recreational Specialization - , Chou, Hsiu- Yueh (Archives of Current Research International, 2020)
The purpose of this study is to analyze the structural relationship among cyclists’ participation motivation; serious leisure and recreational specialization. In this study, cyclists were used as the research object, non-random sampling method was used, and a total of 237 effective questionnaires were collected. After descriptive statistics and partial least squares (PLS) statistics analysis, the results show that: the cyclists’ participation motivation is higher, their characteristics of serious leisure are more obvious, and the recreational specialization also higher; and cyclists have characteristics of serious leisure their recreational specialization is also higher. In addition, the study also confirms that serious leisure has a mediate effect on recreational specialization.